De l’« efficacité » symbolique des interdits à leur fonctionnalité écologique - Hélène Artaud (Revue d'ethnoécologie)
During the last few decades, environmental emergencies as well as mixed results of existing conservation systems, urges researchers and managers of protected areas to look up other forms of resource management models in non-Western cultures. Some cultural features, until recently devoid of rationality (considered “pre-logical” or “illogical”), are suddenly invested with a new intelligibility. The taboo is one of those. Its movement, from the magical ritual sphere to the ecological and normative sphere, causes huge upheaval and underpins the need to restructure environmental management practices and thinking. Which place can occupy, in conservation strategies, complex symbolic systems? What changes, this unprecedented practical requirement implies in terms of anthropological reflection? Based on a wide range of ethnographic and ethno-ecological cases, our analysis will effort to provide answers to these two questions.